Evolution of Nutritional Habits Behaviour of Spanish Population Confined Through Social Media - Mariscal-Arcas, Miguel; Delgado-Mingorance, Sonia; Saenz de Buruaga, Borja; Blas-Diaz, Alba; Latorre, Jose Antonio; Martinez-Bebia, Manuel; Gimenez-Blasi, Nuria; Conde-Pipo, Javier; Cantero, Leticia; Lopez-Moro, Alejandro; Jimenez-Casquet, Maria Jose (Frontiers in Nutrition, 2021)
Introduction: In Spain, on March 14, 2020, a state of alarm is declared in order to face the health emergency situation caused by the COVID-19 coronavirus, limiting the freedom of movement of people. The Spanish population is confined. Objective: With this situation, "NUTRITIONAL HEALTH IS NOT CONFINED" arises a research project that seeks to promote nutritional education based on the pattern of the Mediterranean Diet using new computer technologies. It is about providing the population with information of general interest about the promotion of a healthy diet through social networks and analysing the impact of its dissemination, in the form of a longitudinal intervention study of the Spanish nutritional evolution during confinement, with a daily survey format, it is intended to assess food consumption during the period of confinement. Material and methods: 936 participants were asked every day. Short publications were published every day based on the scientific evidence (FAO, WHO, AECOSAN) through social media such as Instagram, accompanied by a questionnaire of 11 questions (yes/no) where it was intended to assess the evolution of daily consumption. Results and discussion: The diffusion through social media has allowed to have a greater reach of the population. We observed that mood throughout confinement generally improves. There are certain eating habits from the Mediterranean Diet that are well established in the daily diet of our population, such as the consumption of fruits, vegetables, legumes, dairy products and eggs. It seems that enjoying good health is a growing concern in pandemic situations, which is why inappropriate behaviours such as "snacking" between meals or the consumption of processed foods such as snacks, industrial pastries, soft drinks and sweets are avoided, increasing the amount of food healthy like meat and fish. This study opens up future avenues of research promoting Mediterranean Diet and implements new cohort nutritional databases, especially about young adult people, who are adept at navigating digital spaces and therefore using social media.